The The effect of adding fly ash from Labuhan Angin PLTU and bagasse ash from Kwala Madu sugar factory on the compressive strength of high performance concrete - P Yusella; D S J L Tobing; R Aulia; W Wiharti; L E Tanjung (Cered Indonesia Institute, 2026)
Construction work is currently experiencing rapid development in Indonesia, such as building construction, road construction, and bridge construction. Concrete is one of the most widely used construction materials. In concrete technology in Indonesia, concrete that is able to withstand high loads using local materials is very important. The need for concrete mixture materials as the background of this research then conducted experiments in a concrete laboratory to obtain a concrete mixture composition that has high concrete compressive strength capabilities using available local materials. During this experiment, equipment testing, concrete mixture materials, concrete casting, specimen mold preparation, concrete curing, concrete weight checking, slump flow testing, and concrete compressive strength testing were carried out. There were nine variations of concrete mixtures tested, with cube test specimens measuring 5cm x 5cm x 5cm and the test results were then analyzed to draw experimental conclusions. The results showed that the highest concrete compressive strength in a mixture of Fly Ash and Bagasse Ash was in variation 9, namely 50.57 MPa at the age of 3 days. The composition of concrete materials in variation 9 is (Portland Composite Cement (PCC), Silica Fume, Silica Sand Mesh 35-60, Silica Sand Mesh 325, Water, Superplasticizer Viscocrete® 8670 MN, Fly Ash 3.5%, Bagasse Ash 3.5% and Polypropylene Fiber 0.1%). The highest compressive strength value is in variation 8 tested at the age of 28 days, namely 84.66 MPa. so it can be said to be a high-performance concrete. In this study, it was concluded that the use of local materials in the form of Fly Ash from the Labuhan Angin PLTU, and Kwala Madu Langkat Bagasse Ash waste can increase the compressive strength of concrete and can also reduce the impact of pollution on the environment around the waste.